Problematic Pornography Viewing from a Big-5 Personality Perspective. Issue 3 (2nd October 2019) - Borgogna, Nicholas C.; Aita, Stephen L.
Abstract: This study extended prior findings by examining how Big-5 personality traits are related to four dimensions of problematic pornography viewing: functional problems, excessive use, control difficulties, and avoidance of negative emotions. Participants ( n = 569 women and n = 253 men) responded to an online survey. Structural equation modeling indicated that for men, neuroticism was a positive correlate with all dimensions of problematic pornography viewing, extraversion positively correlated with functional problems, excessive use, and control difficulties; and openness-to-experience negatively correlated with functional problems. For women, neuroticism positively correlated with avoidance of negative emotions; openness-to-experience positively correlated with excessive use and use to avoid negative emotions; and conscientiousness negatively correlated with control difficulties. A series of significant interactions across personality dimensions were also observed. Connections to other studies and areas for future research are discussed.